A Sensitive Electrochemical Sensor Based on Dual Co-Doped N, P-rGO for Simultaneous Determination of Hydroquinone and Catechol. Issue 1 (29th January 2021) - Liu, Yanyan; Xie, Ruirui; Zou, Xun; Liu, Jiamin; Wu, Zhiyong; Peng, Chang; Zhao, Peng
Abstract : In this paper, the N and P co-doped reduce graphene oxide (N, P-rGO) was prepared with one-pot solution method and characterized by using SEM and electrochemical technology. It was found that the N, P-rGO has an outstanding conductivity, large surface area and excellent electrocatalytic activity to hydroquinone (HQ) and catechol (CC), which usually coexist in aqueous environment. Under the optimal conditions, compared with bare glassy carbon electrode (GCE) and N doped reduce graphene oxide (N-rGO) modified GCE (N-rGO/GCE), the N, P-rGO/GCE displayed an excellent simultaneous determination towards HQ and CC. And the oxidation peak potential difference of HQ and CC obtained from N, P-rGO/GCE was 106 mV, indicating N, P-rGO/GCE has excellent resolution. The obtained detection limit was 62.1 nM and 99.7 nM for HQ and CC in a concentration range of 1 μ M to 100 μ M, respectively. At the same time, N, P-rGO/GCE also displayed satisfied selectivity, decent stability and desirable reproducibility. Furthermore, the fabricated sensor was successfully applied to detect two isomers in tap water and the recoveries of 99.52% to 106.36% and 95.5% to 103.97% for HQ and CC were obtained, which verified the practical application potential of N, P-rGO/GCE.